Is the Staple Food Consumed Changes in Diabetics can Affect the Quality of Life? A Parallel Randomized Controlled Trial. - Delvarianzadeh 1, Mehri; Nouri 1*, Leila; Mohammadi Nafchi 2, Abdorreza; Ebrahimi 3, Hossein; Khosravi 4, Ahmad (Shahroud Journal of Medical Sciences, 2020)
Backgrounds: Diabetes is one of the chronic diseases that need continual medical care and self-care education, as well as nutritional therapy as an integral part of dietary management. This study was carried out to investigate the effect of bulk bread formulated with portulaca oleracea on quality of life (QOL) in patients with type 2 diabetes.Methods: This parallel randomized controlled trial was conducted on 104 patients with type 2 diabetes. Participants received bulk bread containing 10% portulaca powder for 8 weeks (intervention group); the control group used their normal daily bread. The quality of life score was estimated in both groups by the use of the Short-form 36-Item (SF-36) questionnaire before the intervention, and 8 weeks after dietary intervention, the quality of life score between both groups was compared. The significant level was set at 0.05.Results: The difference in the mean score of quality of life of the studied units in different dimensions of physical function, role limitation due to physical problems, role limitation due to emotional problems, physical pain, social function, energy and vitality, mental health, general health, and overall quality of life showed that there was a significant difference in the mean in all dimensions and quality of life, except mental health, was observed in the case group after the intervention. The mean difference in quality of life in different dimensions before and after the intervention in the intervention group is significant.Conclusions: According to the results, it was revealed that consumption bulk bread formulated with portulaca oleracea can promote the quality of life in patients with type 2 diabetes. So, it can be concluded that portulaca oleracea as a functional plant can be found in bread as a new treatment and prevention method in patients with diabetes.Keywords: Bread, Portulaca oleracea, Quality of life, Type 2 diabetes.